News Coverage of European Press Photo Agency for Crises in Iraq - Abbas Fadhil, Ali (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This research deals with identifying the most important types, forms, themes, contents, sources and websites of visual news coverage of the European Agency for the Journalistic Image (SPA) about the liberation crisis of Mosul for the period 17/10 / 2016 to 7/10/2017, analyzing 1397 photographic images exclusively from this agency. The most important results concluded by the researcher are that the European agency (epa) depends mainly on the informative image in its visual coverage for the Mosul crisis more than with other types of news. He used 1,117 of 1,397 photographic images with a percentage of 79.96